Effect of an Andean culture formulation in a murine model - Huatuco Lozano, Maribel (2021)
The present work aims to determine the effect of a pellet formulation based on Andean crops (arracacha, achira, mashua, oca, cañihua and tarwi) in a murine model as a useful criterion for the design of food products with added value. taking into account the weight and height gain of rodents of the BALB / C-53 strain. Taguchi's methodology was used in the formulation and optimization process, which allowed working with six factors: arracacha (Ar) Arracacia xanthorrhiza, achira (Ac) Canna indica L., mashua (Ma) Tropaeolum tuberosum, oca (Oc) Oxalis tuberosa, cañihua (Ca) Chenopodium pallidiulle aellen, tarwi (Ta) Lupinus mutabilis, with 2 levels of work, for this orthogonal matrix L8 was determined (27). 8 treatment groups were formed for each of the formulations in the form of pellets (F1, F2, F3, F4, F5, F6, F7 and F8) and a control group, the different formulations were administered for 15 days and the control group commercial food (ratonina). The results obtained show that F7 (20% Ar, 20% Ac, 15% Ma, 15% Oc, 20% Ca and 20% Ta) was the most significant in attributing weight, followed by F8 and F2 while F2, F7, and F3 were the most influential in obtaining the height of the mice. Therefore, the most striking effect of the Andean grain formulations with respect to weight and height attribution in a murine model was F7 followed by F2.